2020
DOI: 10.3390/catal10030296
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Metal-Catalyzed Alkyl–Boron (C(sp3)–C(sp2)) Suzuki-Miyaura Cross-Couplings

Abstract: Boron chemistry has evolved to become one of the most diverse and applied fields in organic synthesis and catalysis. Various valuable reactions such as hydroborylations and Suzuki–Miyaura cross-couplings (SMCs) are now considered as indispensable methods in the synthetic toolbox of researchers in academia and industry. The development of novel sterically- and electronically-demanding C(sp3)–Boron reagents and their subsequent metal-catalyzed cross-couplings attracts strong attention and serves in turn to exped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 138 publications
0
36
0
Order By: Relevance
“…The development of synthetic methodology has evolved [ 21 ] to meet the need for preparing 3D-type molecules, including rhodium-catalyzed asymmetric Suzuki–Miyaura reaction with aryls, vinyls, heteroaryls, and heterocycles. Application of the asymmetric sp 2 -sp 3 Suzuki–Miyaura methodology [ 22 ] enabled the synthesis of clinical candidates preclamol ( 15 , a dopamine D2 receptor partial agonist studied for the treatment of schizophrenia), niraparib ( 16 , MK−4827, a 2017 approved poly-(ADP ribose) polymerase (PARP) inhibitor indicated for ovarian cancer), and natural product isoanabasine ( 17 ), which are all presented in Figure 3 with their corresponding Fsp 3 values calculated using SwissADME [ 23 ] online tool.…”
Section: C-c Reaction: Suzuki–miyaura Reactionmentioning
confidence: 99%
“…The development of synthetic methodology has evolved [ 21 ] to meet the need for preparing 3D-type molecules, including rhodium-catalyzed asymmetric Suzuki–Miyaura reaction with aryls, vinyls, heteroaryls, and heterocycles. Application of the asymmetric sp 2 -sp 3 Suzuki–Miyaura methodology [ 22 ] enabled the synthesis of clinical candidates preclamol ( 15 , a dopamine D2 receptor partial agonist studied for the treatment of schizophrenia), niraparib ( 16 , MK−4827, a 2017 approved poly-(ADP ribose) polymerase (PARP) inhibitor indicated for ovarian cancer), and natural product isoanabasine ( 17 ), which are all presented in Figure 3 with their corresponding Fsp 3 values calculated using SwissADME [ 23 ] online tool.…”
Section: C-c Reaction: Suzuki–miyaura Reactionmentioning
confidence: 99%
“…The loading of the catalyst is a key parameter in catalytic applications [ 38 , 39 ]. First, blank adsorption experiments at different pH values in the dark (without exposure to visible light) revealed that the change of initial ethiofencarb concentrations after 12 h of mixing with SnIn 4 S 8 was less than 6% ( Supplementary Materials Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…With the advent of transition metal-catalyzed reactions [ 40 , 41 , 42 , 43 , 44 ], derivatization of preformed pyrrole ring has grown as an alternate strategy for the synthesis of arylated pyrroles. However, preparation of pyrrole-based organometallic reagents employing halogen-metal exchange requires Boc-protection of the acidic N-H proton ( Figure 2 ) [ 45 ].…”
Section: Introductionmentioning
confidence: 99%